Investigation of the anticancer mechanism of monensin via apoptosis‐related factors in SH‐SY5Y neuroblastoma cells - Sema Serter Kocoglu; Ceren Oy; Mücahit Secme; F. Bahar Sunay (Wiley, 2023)
Abstract Monensin is an ionophore antibiotic that inhibits the growth of cancer cells. The aim of this study was to investigate the apoptosis‐mediated anticarcinogenic effects of monensin in SH‐SY5Y neuroblastoma cells. The effects of monensin on cell viability, invasion, migration, and colony formation were determined by XTT, matrigel‐chamber, wound healing, and colony formation tests, respectively. The effects of monensin on apoptosis were determined by real‐time polymerase chain reaction, TUNEL, Western blot, and Annexin V assay. We have shown that monensin suppresses neuroblastoma cell viability, invasion, migration, and colony formation. Moreover, we reported that monensin inhibits cell viability by triggering apoptosis of neuroblastoma cells. Monensin caused apoptosis by increasing caspase‐3, 7, 8, and 9 expressions and decreasing Bax and Bcl‐2 expressions in neuroblastoma cells. In Annexin V results, the rates of apoptotic cells were found to be 9.66 ± 0.01% (p < 0.001), 29.28 ± 0.88% (p < 0.01), and 62.55 ± 2.36% (p < 0.01) in the 8, 16, and 32 μM monensin groups, respectively. In TUNEL results, these values were, respectively; 35 ± 2% (p < 0.001), 34 ± 0.57% (p < 0.001), and 75 ± 2.51% (p < 0.001). Our results suggest that monensin may be a safe and effective therapeutic candidate for treating pediatric neuroblastoma.